2017
DOI: 10.1038/s41467-017-01356-z
|View full text |Cite
|
Sign up to set email alerts
|

History-based action selection bias in posterior parietal cortex

Abstract: Making decisions based on choice-outcome history is a crucial, adaptive ability in life. However, the neural circuit mechanisms underlying history-dependent decision-making are poorly understood. In particular, history-related signals have been found in many brain areas during various decision-making tasks, but the causal involvement of these signals in guiding behavior is unclear. Here we addressed this issue utilizing behavioral modeling, two-photon calcium imaging, and optogenetic inactivation in mice. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
169
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(208 citation statements)
references
References 44 publications
(59 reference statements)
24
169
3
Order By: Relevance
“…In this study, we analyzed the function of PPC and found that the area suppressed the activity of V1 constantly, was related to the neuronal properties of V1, but there are some points to be noted. First, the region of the PPC in this study was ~0.5 mm more medial than what other recent studies identified as the PPC (Driscoll, Pettit, Minderer, Chettih, & Harvey, ; Goard, Pho, Woodson, & Sur, ; Hwang, Dahlen, Mukundan, & Komiyama, ). It has been pointed out that the PPC is composed of two distinct areas (medial and lateral PPC) in rats (Reep & Corwin, ), so it is likely that these may be two functionally distinct areas in mice.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In this study, we analyzed the function of PPC and found that the area suppressed the activity of V1 constantly, was related to the neuronal properties of V1, but there are some points to be noted. First, the region of the PPC in this study was ~0.5 mm more medial than what other recent studies identified as the PPC (Driscoll, Pettit, Minderer, Chettih, & Harvey, ; Goard, Pho, Woodson, & Sur, ; Hwang, Dahlen, Mukundan, & Komiyama, ). It has been pointed out that the PPC is composed of two distinct areas (medial and lateral PPC) in rats (Reep & Corwin, ), so it is likely that these may be two functionally distinct areas in mice.…”
Section: Discussioncontrasting
confidence: 51%
“…Second, in this study we used the artificial stimulus methods for the PPC activation. They may cause the synchronous firing pattern of the PPC which may be different from that in the physiological activation (Driscoll et al., ; Goard et al., ; Harvey, Coen, & Tank, ; Hwang et al., ), although they were able to reveal the PPC function latent under physiological conditions. And finally, the possibility could not be thoroughly ruled out that the incision we made between the PPC to V1 may impact communication between other medial areas and V1.…”
Section: Discussionmentioning
confidence: 96%
“…The most lateral and posterior extent of PPC, area PtP (Paxinos & Franklin, 2012), overlapped partly with anterior area RL. These areas are referred to as "extrastriate", implying a primacy of visual processing (Andermann et al, 2011;Garrett et al, 2014;Marshel et al, 2011;Wang & Burkhalter, 2007), though they overlap considerably with PPC, which has cognitive (Akrami, Kopec, Diamond, & Brody, 2018;Harvey et al, 2012;Hwang et al, 2017;Morcos & Harvey, 2016), navigational (Nitz, 2006(Nitz, , 2012, and movement-related Whitlock et al, 2012) functions that can be expressed independently of visual input. For example, tetrode recordings in unrestrained rats targeting the posterior extent of PPC-appearing to coincide with area AM-showed widespread tuning to self-motion and angular head velocity in addition to visual landmarks (Chen, Lin, Barnes, & McNaughton, 1994;Chen & McNaughton, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For several decades, the monkey has served as the premiere model for investigating the behavioral and neurophysiological contributions of PPC, and while PPC in rodents is substantially smaller and less differentiated, recent years have seen an increase in the use of rats and mice. This has been motivated in part by the fact that rodents can be trained to perform a variety of highly specific, PPC-dependent tasks in real-world and virtual reality settings (Brunton, Botvinick, & Brody, 2013;Goard, Pho, Woodson, & Sur, 2016;Harvey, Coen, & Tank, 2012;Hwang, Dahlen, Mukundan, & Komiyama, 2017;Nitz, 2006;Raposo, Sheppard, Schrater, & Churchland, 2012;Whitlock, Pfuhl, Dagslott, Moser, & Moser, 2012;Wilber, Clark, Forster, Tatsuno, & McNaughton, 2014). The advantages of mice in particular include their genetic tractability and compatibility with large-scale recording and imaging techniques, leading to their widespread usage to study population coding and circuit function in every major sector of cortex, including PPC.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that these assemblies are organized in a hierarchical fashion. First-order sensory areas encode lower-order stimulus features, such as textures coarseness (Chen et al, 2013a;Garion et al, 2014;Safaai et al, 2013), object orientation and direction (Hubel and Wiesel, 1959), and sound frequency (Stiebler et al, 1997), whereas more complex features and contextual aspects of a stimulus are encoded by higher-order cortices (Akrami et al, 2018;Felleman and Van Essen, 1991;Hwang et al, 2017;Pho et al, 2018). Nonetheless, the coding in primary sensory cortices can exhibit higher levels of complexity, expressing non-sensory-related signals such as attention (Francis et al, 2018), anticipation (Poort et al, 2015) and behavioral choice (Chen et al, 2015;Francis et al, 2018;Pho et al, 2018;Poort et al, 2015;Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%